Penggunaan Media Sosial Sebagai Sarana Pendidikan Politik - Nurlatifa Nurlatifa; Syamzaimar Syamzaimar (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the role of social media as a medium for political education in the digital era, examine the effectiveness of political content spread through various social media platforms, and identify the challenges that arise in its implementation. The research employs a qualitative approach with literature review method, utilizing primary and secondary sources from academic journals, books, and relevant documents published between 2020 and 2025. The findings reveal that social media platforms such as Instagram, Twitter/X, YouTube, and TikTok have transformed the landscape of political education, particularly among the younger generation. Social media facilitates broad and rapid dissemination of political information, encourages political participation, and enables interactive two-way communication between the public and political actors. However, the spread of hoaxes, political polarization, and digital literacy gaps remain significant challenges. This research concludes that optimizing social media as a tool for political education requires collaboration between the government, educational institutions, and media platforms to create a healthy, educative, and participatory digital political ecosystem.